A study of psychological well being, satisfaction with life, and levels of anxiety among triathletes - Crisanti, A. S.; Hiller, W. D. B.; Dierenfield, L. M. (2001)
The sport of triathlon is a supreme test of physical and mental capabilities. Participation in this event requires enormous time, energy, and commitment, and individuals attracted to the sport likely have certain personality characteristics conducive to training for, participating in, and completing such an extreme test of endurance. The purpose of this study is twofold. The first objective is to learn more about the types of personalities among a triathlon population. Because of the extreme level of commitment and level of physical and mental endurance required by the sport, the second objective is to examine the impact of triathlon on participants lives by examining reported satisfaction with life and levels of anxiety associated with the sport. A cross-sectional design will be used and subjects will be selected from an Olympic distance triathlon, and a HaIf-Ironman competition, both of which are qualifying races for the World Triathlon Championships in Kona, Hawaii. Standardized instruments will be used to collect the data, including the: (1) Structured Clinical Interview Screening Tool, (2) Satisfaction with Life Scale, and (3) Sports Competition Anxiety Test. Results of the study will be presented and implications of the findings will be discussed.